Group 4 imido complexes stabilized by a tridentate diamido-donor ligand - Blake, A; Collier, P; Gade, L; Mountford, P; Lloyd, J; Pugh, S; Schubart, M; Skinner, M; Trosch, D (2001)
Reaction of the lithium amides [(2-C5H4N)C(CH3){CH2N(Li)SiMe 3}2]2 (2a) and [(2-C5H4N)C(CH3){CH2N (Li)-SiMe2tBu}2]2 (2b) with the imidotransition metal complexes [Ti(NtBu)Cl2(py)3], [Ti(N-2,6-C6H3iPr2)Cl2(py) 3], and [Zr(N-2,6-C6H3iPr2)Cl2(thf) 2] yielded the five-coordinate imido-titanium and -zirconium complexes [{κ3N-(2-C5H4N)C(CH3)(CH 2NSiMe2R)2}Ti(NR′)(py)] (R = Me, R′ = tBu: 3a, R= tBu, R′ = tBu: 3b, R = Me, R′ = 2,6-C6H3iPr2: 4a, R = Me, R′ = 2,6-C6H3Me2: 4b) and [{κ3N-(2-C5H4N)C(CH3)(CH 2NSiMe3)2}Zr(N-2,6-C6H 3iPr2)(py)] (5). The tridentate diamido-pyridine ligand adopts a facial coordination mode in the distorted trigonal bipyramidal complexes with the imido ligand occupying an equatorial position, as was established by X-ray diffraction for 3a and 5. Sublimation of 3a and 4a yielded the pure four-coordinate imidotitanium complexes [{κ3N-(2-C5H4N)C(CH3)(CH 2NSiMe3)2}Ti(NR′)] (R′ = tBu: 6, 2,6-C6H3iPr2: 7) which were structurally characterized by X-ray crystallography. Reaction of 3a with the Lewis acid B(C6F5)3 also led to abstraction of the axially bound pyridine ligand and the formation of the adduct [py-B(C6F5)3] and 6. Reaction of 6 with thf, PMe3, and pyridine led to the formation of pentacoordinate complexes [{κ3N-(2-C5H4N)C(CH3)(CH 2NSiMe3)2}-Ti(NtBu)(thf)] (8), [{κ3N-(2-C5H4N)C(CH3)(CH 2NSiMe3)2}Ti(NtBu)(PMe3)] (9), and [{κ3N-(2-C5H4N)C(CH3)(CH 2-NSiMe3)2}Ti(NtBu)(py)] (3a) in which the donor ligands occupy axial positions.